Knowledge and practices on sustainable diets in families in Monteverde, Costa Rica 2021 - Del Valle-Alvarado, María Rebeca (2025)
Introduction: Education for sustainability aims to promote decision-making and actions aligned with the Sustainable Development Goals (SDGs). To promote sustainable diets, a diagnostic analysis is key to identifying demographic characteristics, practices, knowledge, and opinions of the target population. This information is necessary for the formulation of a contextualized and timely educational strategy that can influence eating behaviors. In this sense, the objective of this study is to analyze the knowledge, attitudes, and practices of local families regarding sustainable diets. Methodology: Descriptive study with a mixed approach involving 23 families from the Monteverde district. Results: The majority of interviewees recognize the influence of food on the environment and the community's economy. However, there is a need to reinforce the role of consumers in the transformation of food systems, with the purpose of encouraging norms and values through critical thinking and reflection, which can motivate the adoption of more sustainable diets. In some cases, the knowledge did not reflect in the practices carried out. Conclusions: Considering the need for sustainability education to be contextualized, this diagnosis should be used as the starting point to inform about the principles of sustainable eating and facilitate the development of competencies, with the goal of helping participants create their own action plan to adopt a sustainable diet.